Petrological Features of the Burlakski and Nizhne-Derbinsk Mafic-Ultramafic Plutons (East Sayan Mountains, Siberia, Russia); Minerals; Vol. 10, iss. 2 - Yakich T. Yu. Tamara Yurievna; Brzozowski M. J. Matthew Jacek; Chernyshov A. I. Aleksey Ivanovich; Savinova O. V. Olesya Vyacheslavovna; Timkin T. V. Timothy Vasilyevich; Marfin A. E. Aleksandr Evgenjevich (2020, 2020)
Title screen